The use of Dupont Model in the Analysis of the Company's Performance : A Case Study - SAIDI, Ahlem; BENMOUFFEKI , Ali (Journal of Research in Finance and Accounting, 2026)
This study aimed to identify the extent to which Algerian corporations are aware of the importance of using appropriate mechanisms and methods when evaluating their performance, in addition to knowing the obstacles that prevent them from owning these mechanisms. The study relied on the DuPont model, which is an analysis that measures the company's performance and shows changes, if they occur, and whether they are good or bad. The model is based on the analysis of Return on Equity (ROE) & Return on Investment (ROI). In order to achieve the objectives of the study, it was relied on a case study of an economic corporation acting at the level of the state of M'sila, where several results were reached, the most important of which is that there is a clear awareness of the importance of performance analysis in maintaining the corporation continuity, with a lack of use of some modern methods of analysis such as the DuPont model